A Rare Presentation of Acute Multifocal Skeletal Multidrug-resistant Tuberculosis - Rahul Puli; Sujatha Ramabhatta; Lakshmipathy Suddekunte Rajagopaliah; Raghunandan Bambhore Gopala Krishna Murthy Rao; Rashmi Khatawkar; Anusree Krishnan (Pediatric Infectious Disease)
Tuberculosis (TB) involving the musculoskeletal system is unusual. An acute and multifocal noncontiguous presentation is diagnostically challenging as it simulates various other infections, hematological malignancies, and secondaries. In this study, we report a rare record of a 14-year-old girl who presented with multiple focal swellings on her body within a short duration of 6 days. The tuberculin skin test was exaggerated and the cartridge-based nucleic acid amplification test (CBNAAT) of the granulomatous aspirate revealed rifampicin-resistant TB. Magnetic resonance imaging (MRI) showed swellings with underlying bone erosions and cultures of pus aspirate from the right shoulder region turned out to be Rifampicin and Isoniazid resistant TB.